Edaphic macrofauna associated with the cultivation of maize (Zea maiz) - Segundo Chávez-Quintana; Roxana Hurtado-Burga; Manuel Milla-Pino; Tito Sanchez-Santillán; Erik Martos Collazos-Silva (Journal of the Selva Andina Biosphere)
Macrofauna is a biological indicator of soils, in this sense, the objective of this research was to determine the edaphic macrofauna community and its physicochemical properties of the soil, by means of its abundance and richness of groups during the growing season and post-harvest of corn. Three monoliths 25 x 25 cm wide by 30 cm deep were established. Soil samples were taken in each plot, then the organic matter (OM) content, hydrogen potential (pH), electrical conductivity (EC) and nitrogen (N) content were determined. The results show differences between atmospheric temperatures during the development period (25 °C) and the post-harvest period (41.4 °C). Physicochemical parameters such as pH ranged between 8.5 and 8.3. The maximum Shannon index was 0.48 (growing season) and 0.13 (post-harvest season). The greatest number of individuals was ants (111) and was identified during the post-harvest period. In this sense, the biological diversity was lower in the growing season of corn, and during the post-harvest period a greater number of ant organisms was determined, which was associated with the resistance to high temperatures.